Predictive value of the quantitative flow ratio after pretreatment and drug-coated balloon therapy for functional stenosis of target vessels at the mid-term follow-up - Lin, Xinjun; Chen, Yuwei; Huang, Wanjun; Cheng, Zhendong; Yu, Bin; Ji, Wei; Wang, Yaoguo; Xu, Chaoxiang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDrug-coated balloon (DCB) treatment requires adequate preconditioning of target lesions. The quantitative flow ratio (QFR) is an emerging method for assessing functional stenosis of coronary arteries. This study investigated the predictive value of the QFR after pretreatment and DCB treatment for functional stenosis of the target vessel at the mid-term follow-up.MethodsThe study included patients with coronary heart disease who received DCB treatment. The patients were divided into two groups based on their functional stenosis status at follow-up. Independent predictors associated with functional stenosis and the effects of the pretreatment QFR on outcomes were investigated. A receiver operating characteristic curve analysis was used to determine the pretreatment QFR cutoff value associated with follow-up QFR >0.80. The mediating effects of the QFR after pretreatment and DCB treatment on outcomes were also examined.ResultsThe study included 97 target vessels from 97 patients; the median follow-up time was 297.0 days. The high (QFR >0.80) and low (QFR ≤0.80) QFR groups included 78 and 19 vessels, respectively. Multifactor logistics regression analysis identified the pretreatment QFR as an independent predictor of outcome. The pretreatment QFR cutoff value for predicting functional stenosis was 0.705. The DCB-treatment QFR did not elicit mediating effects on the follow-up QFR.ConclusionsThe QFR after pretreatment directly and significantly affected the follow-up QFR. Pretreatment QFR <0.705 may be a valuable predictor of functional stenosis after DCB treatment.